Effect of fulvic acid on the growth of hydroponic pea (Pisum sativum L.) microgreens - Gutiérrez , Aldo; Balandrán, Martha; Yáñez, Rosa; Hernández, Jared (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
Fulvic acid is a widely recognized biostimulant due to its benefits in traditional crops; however, its application in hydroponic systems, particularly in microgreen production, is not well documented. This study evaluated the effect of fulvic acid on the growth of hydroponic pea microgreens (Pisum sativum L.). The experimental design was completely randomized and consisted of four treatments (n=5): nutrient solution (NS), fulvic acid solution 0.01 % (FA), NS + FA, and water (control). After 12 days, growth and biochemical parameters were measured. The results showed that NS and NS+FA treatments significantly increased stem length (7.73 cm and 7.28 cm), fresh weight (0.613 g and 0.618 g), and yield (6.15 kg.m-2) compared to the FA treatment or control. The FA treatment increased stem diameter (2.38 mm) but did not significantly increase biomass. Biochemical analysis showed that FA and control had higher nitrate content, while NS and NS+FA reduced nitrate accumulation. Antioxidant capacity, chlorophyll content, and color index were similar among treatments. However, the pH increased with the application of fulvic acid. Fulvic acid alone moderately improved growth but was less effective than the nutrient solution. The combination of fulvic acid with a complete nutrient solution did not produce additive effects, highlighting the importance of balanced nutrition in hydroponic microgreen production.